A aplicação do Método PBL (Problem Based Learning) para o Curso de Contabilidade no Ensino Superior: suas vantagens e desvantagens - Cassaro, Maria Cristina Alves (2017)
Evolution in business scope has expanded significantly all over the sectors and the start of a professional career depends on a very relevant factor called teaching and learning, which is the basis for a successful profession. In order to occur improve-ments in accounting education area, actions which comprise the factors that influ-ence the evolution of learning and teaching are needed. This work aimed to analyze the PBL (Problem Based Learning) methodology, to identify possible contributions to the teaching learning process in the course of Accounting Sciences. The research employs a quantitative approach with the objective of collecting data in a given popu-lation, using a closed questionnaire that serves as sampling for the procedure of analysis and interpretation of data for the present study. As a result, it can be con-firmed, among some aspects, that the PBL methodology is preferred by teachers and students. With this, it was observed in the research that such method is applicable in the course of Accounting Sciences, respecting the literary support, so that it can suc-ceed in the development and application of a new methodology of teaching used in the classroom, so that the student Develop critical thinking, logical reasoning, initia-tion to research, group work, problem solving skills proposed